Sharia Fintech: Horizon of MSME Financing in Indonesia - Imama Zuchroh (UNIVED Press, 2022)
This research aims to present shariah fintech into a horizon of hope of potential financing instruments for MSMEs. The impact of the covid-19 outbreak has caused some business activities to slow down and MSMEs are economic activities that have a deep impact. With sharia fintechk can be a supporter of the revival and development of MSMEs. Because MSMEs have a big role as the backbone of economic growth. Methodology: In this study, the research method used is descriptive analysis using a qualitative approach. The data that has been collected is used as secondary data, then analyzed together by conducting a literature study There are some obstacles in developing sharia fintech in encouraging the growth of MSMEs in Indonesia. These obstacles can be solved with two strategies. First, strengthening the ecosystem in the form of synergy between sharia fintech, fintech service, sharia banking, the government which is a regulator, and among universities as academics. Second, it takes massive and targeted socialization and promotion of the existence of sharia fintech so that MSMEs know alternative funding instruments that are relatively easier to access and process.